Searching images by using color structure - Rafayel V. Barseghyan (Изд-во НАН РА)
In this paper a color-structured image search method is proposed which allows to classify large image collections by color and quickly ¯nd the interested images. According to the proposed method a software system is developed that demonstrates the e±ciency and accurancy of the proposed method.
Keywords: Mathematics; Computer software